56.0k views
0 votes
NO LINKS!!!!!!
Write in graphing form x^2 + 10x + y^2 - 6y = 2

1 Answer

7 votes

9514 1404 393

Answer:

(x +5)^2 +(y -3)^2 = 36

Explanation:

Add the squares of half the linear term coefficients, then rewrite using squares. You get the standard form equation of a circle.

x^2 +10x +y^2 -6y = 2

(x^2 +10x +5^2) +(y^2 -6x +(-3)^2) = 2 +5^2 +(-3)^

(x +5)^2 +(y -3)^2 = 36 . . . . . circle centered at (-5, 3) with radius 6

NO LINKS!!!!!! Write in graphing form x^2 + 10x + y^2 - 6y = 2-example-1
User Simo Salminen
by
5.4k points